Creating German communism, 1890-1990 : from popular protests to socialist state - Weitz, Eric D. (Princeton University Press, 1997)
This social and political history of German communism ranges from its origins in imperial Germany to the collapse of the German Democratic Republic in 1990. The Weimar period is seen as crucial is forging a style of politics that contributed to the intransigence of the GDR during its history.
Keywords: Kommunistische Partei Deutschlands -- Histoire.; Communism -- Germany -- History.; Communism -- Germany (East) -- History.; Germany -- Politics and government -- 1871-; Germany (East) -- Politics and government.; Communisme -- Allemagne -- Histoire.; Communisme -- Allemagne (Est) -- Histoire.; Allemagne -- Politique et gouvernement -- 1871-; Allemagne (Est) -- Politique et gouvernement.; HISTORY -- Europe -- Germany.; Communism; Politics and government; Germany; Germany (East); Communisme.; KPD.; SED.; Communisme -- Allemagne (République démocratique) -- Histoire.; Allemagne (République démocratique) -- Politique et gouvernement.; Allemagne -- Politique et gouvernement -- 1871-.; Allemagne (est) -- Politique et gouvernement.; Since 1871; History